PEDAGOGICAL ACTIVITY AND ITS CHARACTERISTICS - Zakirov Mirzarakhim Abdualiyevich . (Western European Studies, 2024)
This in the article pedagogue - teacher , teacher young to generation education to give with engaged in person as , education process learner and this the process manage problems with engaged in expert as embodiment light up given
Keywords: Pedagogue; teacher; person